ADAPTATION OF ORGANIZATIONAL CULTURE IN SUPPORTING DIGITAL TRANSFORMATION IN ACCOUNTING - Ali, Ali Umar; Hasanah, Uswatun (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This study aims to examine the role of organizational cultural adaptation in supporting digital transformation in accounting through a literature review. The research employs a literature review method by analyzing relevant articles and academic journals from reputable sources. The primary focus is identifying organizational cultural factors that contribute to successful digital transformation, such as leadership, digital competency development, and innovation. The findings from the literature review indicate that an adaptive organizational culture that fosters innovation and employee empowerment significantly influences the success of digital technology implementation. Moreover, cultural barriers, such as resistance to change, are often the primary obstacles in the digital transformation process. In conclusion, organizational cultural adaptation, including openness to innovation, leadership that supports change, and continuous digital skill development, is crucial in facilitating digital transformation in accounting.